4-(2,5-Dimethyl-1H-pyrrol-1-yl)-1,2,5-oxadiazol-3-amine - Natalia V. Obruchnikova; Oleg A. Rakitin (Molbank, 2023)
1,2,5-Oxadiazol-3-amines with a heterocyclic substituent in the 4-position are being intensively investigated as compounds with valuable pharmacological activity. In this communication, the reaction of 1,2,5-oxadiazole-3,4-diamine with 2,5-hexanedione was shown to selectively give 4-(2,5-dimethyl-1H-pyrrol-1-yl)-1,2,5-oxadiazol-3-amine as a product of the Paal–Knorr reaction. The structure of the synthesized compound was established by elemental analysis, high-resolution mass spectrometry, 1H and 13C NMR, and IR spectroscopy.